Interspecific variation in defense secretions of Malaysian termites from the genusNasutitermes (Isoptera, nasutitermitinae) - Chuah, Cheng Hock; Goh, S.H.; Tho, Y.P. (Springer Verlag, 2013)
The defense secretions of five species of MalaysianNasutitermes,N. longinasus, N. matangensis, N, havilandi, N. johoricus, andNasutitermes species 01, are compared.N. longinasus andN. species 01 provide trinervitene alcohols,N. havilandi mainly tricyclic trinervitene and tetracyclic kempane alcohols and acetates, whereasN. matangensis furnish acetyl/propionyl derivatives of trinervita-11(12),15(17)-dien-3α,9β,13α-triol (XXI and XXII). A new diterpene, assigned as trinervita-11(12),15(17)-dien-3α,13α-diol-3,13-O-diacetate (XVII), is isolated fromN. havilandi. The mono- and diterpenoid compositions, being species-specific, are useful for chemotaxonomic and phylogenetic studies.